Commentary on Zicari. Expressive Tempo Modifications in Adelina Patti’s Recordings: An Integrated Approach - Ross, Jaan (Empirical Musicology Review, 2017)
In this commentary, statistical and sound signal segmentation methods as applied in Massimo Zicari's "Expressive tempo modifications in Adelina Patti's recordings: An integrated approach" are discussed. A potential method of further analyzing the obtained data is also highlighted.